SUPPORTING ONLINE ADJUNCT FACULTY: A VIRTUAL MENTORING PROGRAM - Puzziferro-Schnitzer, Maria; Kissinger, Jeff (Online Learning, 2005)
Because of growing demand for online courses, staffing and faculty support issues can become major obstacles to growth and instructional quality. In 2004, Florida Community College at Jacksonville (FCCJ) was awarded an Effective Practices Award at the Sloan-C conference in Orlando, Florida for its Virtual Adjunct Mentoring program. This paper will provide the background, current program organization, and future directions of the program.